2015
DOI: 10.1002/chir.22508
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Enantiomers of a Phospholipid in Langmuir Monolayers by a New Selector

Abstract: Chiral discrimination in a racemic mixture of dipalmitoylphosphatidylcholine (DPPC) is induced by a new selector at the water-air interface: L-DPPC is segregated in the condensed phase of a Langmuir monolayer upon interactions with an enantiopure amphiphilic compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Brewster angle microscopy images at the water‐air interface for Langmuir monolayers D‐DPPC (A) and D,L ( racemic )‐DPPC (B) . D‐DPPC enantiomer forms multilobar patterns (A), the shape of which is directly correlated with the absolute configuration, while racemic DPPC does not exhibit a chiral pattern (B).…”
Section: Glycerophospholipids and Their Enantiomersmentioning
confidence: 93%
See 4 more Smart Citations
“…Brewster angle microscopy images at the water‐air interface for Langmuir monolayers D‐DPPC (A) and D,L ( racemic )‐DPPC (B) . D‐DPPC enantiomer forms multilobar patterns (A), the shape of which is directly correlated with the absolute configuration, while racemic DPPC does not exhibit a chiral pattern (B).…”
Section: Glycerophospholipids and Their Enantiomersmentioning
confidence: 93%
“…A Brewster angle microscopy study revealed that the monolayer membrane of DPPC enantiomers (Figure ) forms multilobar or rosette assemblages in a stereochemistry‐dependent manner . Different domain shapes were observed depending on the compression rate.…”
Section: Glycerophospholipids and Their Enantiomersmentioning
confidence: 99%
See 3 more Smart Citations